A ∗ = A ÷ A + A × A − A
Evaluate:
1 0 ∗ − 9 ∗ + 8 ∗ − 7 ∗ + 6 ∗ − 5 ∗ + 4 ∗ − 3 ∗ + 2 ∗ − 1 ∗
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
A ∗ = A ÷ A + A × A − A = 1 + A ( A − 1 ) 1 0 ∗ − 9 ∗ + 8 ∗ − 7 ∗ + 6 ∗ − 5 ∗ + 4 ∗ − 3 ∗ + 2 ∗ − 1 ∗ 1 + 1 0 × 9 − ( 1 + 9 × 8 ) + 1 + 8 × 7 − ( 1 + 7 × 6 ) + 1 + 6 × 5 − ( 1 + 5 × 4 ) + 1 + 4 × 3 − ( 1 + 3 × 2 ) + 1 + 2 × 1 − ( 1 + 1 × 0 ) 1 + 1 0 × 9 − 1 − 9 × 8 + 1 + 8 × 7 − 1 − 7 × 6 + 1 + 6 × 5 − 1 − 5 × 4 + 1 + 4 × 3 − 1 − 3 × 2 + 1 + 2 × 1 − 1 − 1 × 0 1 0 × 9 − 9 × 8 + 8 × 7 − 7 × 6 + 6 × 5 − 5 × 4 + 4 × 3 − 3 × 2 + 2 × 1 − 1 × 0 9 ( 1 0 − 8 ) + 7 ( 8 − 6 ) + 5 ( 6 − 4 ) + 3 ( 4 − 2 ) + 1 ( 2 − 0 ) = 1 8 + 1 4 + 1 0 + 6 + 2 = 5 0
One can simplify A* to equal 1 + A 2 − A We now have the equation: ( 1 + 1 0 2 − 1 0 ) − ( 1 + 9 2 − 9 ) + . . . + ( 1 + 2 2 − 2 ) − ( 1 + 1 2 − 1 ) = ?
The constant 1 is both added and subtracted 5 times, so in the end, it cancels itself out. Because it is negligible, a modified equation could be:
(10^2 - 10) - (9^2 - 9) +... + (2^2 - 2) - (1^2 - 1)=?]
We can now rearrange this to be:
( 1 0 2 − 9 2 + . . . + 2 2 − 1 2 ) − ( 1 0 − 9 + . . . + 2 − 1 ) = ?
We can substitute 1 0 2 − 9 2 + . . . + 2 2 − 1 2 with 5 ( 6 2 − 5 2 ) which equals 5 ( 1 1 )
We can also substitute 1 0 − 9 + . . . + 2 − 1 with 5 ( 6 − 5 ) which equals 5 ( 1 )
Our equation now is 5 ( 1 1 ) − 5 ( 1 ) = 5 ( 1 0 ) = 5 0 = ?
Problem Loading...
Note Loading...
Set Loading...
First, A ∗ = A 2 − A + 1
Then, say B = A − 1
Then, B ∗ = A 2 − 3 A + 3
Thus, A ∗ − ( A − 1 ) ∗ = 2 ( A − 1 ) = 2 B
So, 1 0 ∗ − 9 ∗ + 8 ∗ − 7 ∗ + 6 ∗ − 5 ∗ + 4 ∗ − 3 ∗ + 2 ∗ − 1 ∗
is equal to 2 ( 9 + 7 + 5 + 3 + 1 ) = 2 × 2 5 = 5 0